Crotchet Castle - Peacock, Thomas Love, 1785-1866 (Salt Lake City, UT : Project Gutenberg, 2000)
"Crotchet Castle" by Thomas Love Peacock is a novel published in 1831. The story assembles a collection of eccentrics, each obsessed with peculiar notions, generating humor through their clashing conversations. Among them are a clergyman suspicious of intellectual progress, a romantic who believes civilization peaked in the twelfth century, and a cynical lady determined to marry for money. The action unfolds during a house party and a journey toward Wales, culminating in a parody of contemporary riots. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Crotchet_Castle
Release date is 2000-02-01
Transcribed from the 1887 Cassell & Company edition by David Price
Keywords: Authors -- Fiction; England -- Fiction; Philosophy -- Fiction